Invasion Risk and Potential Impact of Alien Freshwater Fishes on Native Counterparts in Klang Valley, Malaysia - Abdulwakil Olawale Saba (MDPI AG, 2021)
This study explores the potential effects of alien fishes on the native fish community, well-being, and tropic preferences in selected rivers of Klang Valley, Malaysia. Following the Aquatic Species Invasiveness Screening Kit assessment, most of the alien fishes (80%) are invasive. The alien species occurrences correlated positively (p < 0.05) with poor water quality, such as rivers with high ammonia-nitrogen and nitrite, but negatively with phosphate and dissolved oxygen. Anthropogenic characteristics, such as rivers with high pollution levels and ease of accessibility to the fish habitat, are mainly associated positively (p < 0.05) with the occurrences of alien fish species. In general, the results of fish stomach contents analyses and their associated indices, together with stable carbon and nitrogen isotopes, revealed domination by alien fishes or diet overlaps between both alien and native fish species. This finding indicates that alien fishes benefited from the impacts of the anthropogenic activities in their surrounding habitats, while their plasticity in feeding habits might help them to invade, survive, and dominate in the rivers of Klang Valley, Malaysia.